Subxiphoid, Nonintubated, Opioid-Free, Video-Assisted Pneumonectomy: A New Frontier in Thoracic Surgery. Issue 6 (November 2021) - Nizami, Maria; Hogan, John; Ali, Jason M.; Vokshi, Ismail; Patvardhan, Chinmay; Peryt, Adam; Coonar, Aman; Aresu, Giuseppe
Surgical approaches to major pulmonary resections have evolved from thoracotomy to multiportal video-assisted thoracoscopy (VATS) and subsequently uniportal VATS. The efficacy of this progress has been validated in a multitude of publications demonstrating reductions in complications, patient perception of pain, and postoperative length of stay. More recent advances include subxiphoid extrathoracic access and nonintubated, opioid-free anesthesia. Early publications have demonstrated promising results with respect to safety, technical feasibility, and enhanced recovery. However, there remains a paucity of literature relating to hybrid approaches comprising both subxiphoid and nonintubated, opioid-free anesthesia in the context of pneumonectomy. The current report is the case of a patient undergoing pneumonectomy. Both subxiphoid and nonintubated, opioid-free techniques were utilized. The authors describe preoperative workup, surgical and anesthesia-related caveats, and postoperative recovery. In conclusion, this approach is technically feasible, safe, and may be associated with enhanced recovery.